Evaluating the effects of physical reactions on aggression via concurrent‐operant analyses. Issue 3 (29th March 2019) - Hood, Stephanie A.; Rodriguez, Nicole M.; Luczynski, Kevin C.; Fisher, Wayne W.
Abstract : Under naturally occurring conditions, the individual who is the target of aggression is likely to physically react to evade the aggressor and avoid physical harm. Like other forms of attention that occur following problem behavior, physical reactions may maintain problem behavior. However, evaluating the effects of physical reactions is complicated by issues related to therapists' ability to consistently and safely control their reactions, which may prove difficult to achieve in functional analyses. We evaluated the utility of a concurrent‐operant analysis to test behavioral sensitivity to physical reactions. The results suggest that the concurrent‐operant analysis may be useful when therapists cannot consistently refrain from responding contingent on problem behavior in the control condition of a more typical functional analysis.